Obstacles to Covenantal Pluralism in Contemporary Russia - Dunajeva, Jekatyerina (The review of faith & international affairs, 2025)
What are the prospects for covenantal pluralism in Russia? Despite constitutional guarantees of religious freedom and the state’s recognition of its multi-confessional and multi-ethnic character, this article argues that Russian religious communities face a hierarchical system that divides religious groups between “traditional” and “non-traditional” faiths. This religious hierarchy creates an uneven playing field where non-traditional faiths tend to experience greater legal restrictions and societal pressures. Drawing on fieldwork in Russia, the article explores how Christian minorities experience religious freedom and negotiate politicized labels of traditional and non-traditional faiths. The article concludes that there are significant barriers to covenantal pluralism in Russia.